2021
DOI: 10.3390/su13116148
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences on Psychosocial Factors Affecting COVID-19 Preventive Behaviors

Abstract: Previous studies have reported differences between men and women in the adoption of preventive behaviors against infectious diseases. This study aims to examine gender differences on a set of psychosocial factors shown to influence preventive behaviors against infectious diseases such as COVID-19. We conducted a web survey (N = 1.004) a few weeks after the end of the peak of the first wave of infections in Chile. The survey assessed participants’ perception of risk and worry about the COVID-19 pandemic, confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 56 publications
10
25
1
Order By: Relevance
“…The literature (incl. [80][81][82][83]) emphasises that women are more susceptible to changes caused by crises (economic, climatic, and social) and are more vulnerable to their effects, which persist much longer for women than for men. In the context of the labour market, it is women that will be laid off first [41], which renders the reversal of the mechanism of dependence of the female labour market on the male labour market, such as what happened in the textile industry, unlikely to repeat.…”
Section: Discussionmentioning
confidence: 99%
“…The literature (incl. [80][81][82][83]) emphasises that women are more susceptible to changes caused by crises (economic, climatic, and social) and are more vulnerable to their effects, which persist much longer for women than for men. In the context of the labour market, it is women that will be laid off first [41], which renders the reversal of the mechanism of dependence of the female labour market on the male labour market, such as what happened in the textile industry, unlikely to repeat.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that women are more likely to engage in preventive behaviors, [23,24] including towards COVID-19. [25,26] Men may also be more likely to engage in risk taking behavior, [27] whereas women are more risk averse. [28] Practicing COVID-19 prevention behaviors was also positively associated with living in a rural vs. urban area.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, this study was conducted in China and thus limited to this context only. Future studies could be replicated in other countries [43] to examine and compare the key similarities and differences that contribute toward extending the literature.…”
Section: Limitations and Future Researchmentioning
confidence: 99%